Genetic Polymorphisms of Cyp19 and Myostatin Genes in Turkish Indigenous Sheep Breeds - AKIŞ, I.; ESEN GÜRSEL, F.; HACIHASANOĞLU ÇAKMAK, N.; ATMACA, G.; YARDIBI, H.; ATEŞ, A.; DURAK, M. H.; ÖZTABAK, K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Growth and meat production traits are very important in sheep breeding. Cyp19 gene has a major role in reproductive activity and growth due to its function in estrogen synthesis. Another gene affecting growth traits is Myostatin (MSTN) gene, which mainly regulates skeletal muscle growth. In this study allele frequencies of genetic polymorphism in Cyp19 and Myostatin genes were identified by PCR-RFLP method in five indigenous Turkish sheep breeds, Chiose, Imroz, Kivircik, Zom and Morkaraman. Digestion of Cyp19 gene with HaeIII only revealed uncut AA genotype and digestion of MSTN with DraI also revealed only uncut AA genotype. Both loci analyzed in this study were found to be monomorphic in five Turkish indigenous sheep breeds. These highly conserved parts of the two genes can be useful for molecular evolutionary studies in sheep. Further studies regarding association analysis of Cyp19 and MSTN in sheep should be conducted.